Functional Impairment of Mononuclear Phagocyte System by the Human Respiratory Syncytial Virus - Bohmwald, Karen; Espinoza, Janyra A.; Pulgar, Raúl A.; Jara, Evelyn L.; Kalergis, Alexis M. (Frontiers in Immunology, 2017)
ABSTRACT The mononuclear phagocyte system (MPS) comprises monocytes, macrophages (M) and dendritic cells (DCs). MPS is part of the first line of immune defense against a wide range of pathogens, including viruses, such as the human Respiratory Syncytial Virus (hRSV). The human RSV is an enveloped virus that belongs to the Pneumoviridae family, Orthopneumovirus genus. This virus is the main etiological agent causing severe acute lower respiratory tract infection (ALRTI), especially in infants, children and the elderly. HRSV can cause bronchiolitis and pneumonia and it has also been implicated in the development of recurrent wheezing and asthma. Monocytes, M and DCs significantly contribute to acute inflammation during hRSV-induced bronchiolitis and asthma exacerbation. Furthermore, these cells seem to be an important component for the association between hRSV and reactive airway disease (RAD). After hRSV infection, the first cells encountered by the virus are respiratory epithelial cells, alveolar macrophages (AMs), DCs and monocytes in the airways. Because, AMs constitute the predominant cell population at the alveolar space in healthy subjects, these cells work as major innate sentinels for the recognition of pathogens. Although adaptive immunity is crucial for viral clearance, alveolar macrophages are required for the early immune response against hRSV, promoting viral clearance and controlling immunopathology. Furthermore, exposure to hRSV may affect the phagocytic and microbicidal capacity of monocytes and Ms against other infectious agents. Finally, different studies have addressed the roles of different DC subsets during infection by hRSV. In this review article, we discuss the role of the lung MPS during hRSV infection and their involvement in the development of bronchiolitis.